Síntese e avaliação de compostos β-aminocarboxílicos como modificadores da neurotransmissão glutamatérgica - Luchez, Cibele Venancio [UNIFESP] (2017)
L-glutamate is the most abundant amino acid in the brain, responsible for mediating most rapid synaptic transmissions, and is involved in many aspects of normal brain functions such as motor, fear, learning, and memory. Dysfunctions of the glutamatergic system affect these actions leading to several diseases of neurological and / or psychiatric order. Compounds with a β-aminocarboxylic structure (series LINS04) were designed from the structure of L-aspartate and DL-TBOA with the objective of exploring their functional role in glutamatergic synaptic transmission, and may later be applied as drugs in the treatment of Central nervous system involving such a system. The compounds were prepared from the ethyl acetoacetate, which was converted to the corresponding enamines followed by reduction, yielding the β-amino ester compounds LINS04005 and LINS04006 in good yields. These compounds were then hydrolyzed to provide β-aminocarboxylic acids LINS04008 and LINS04009 in moderate yields. These compounds were tested by electrophysiological assays in hippocampal slices of wistar rats in order to investigate their effects on gluatamatergic transmission. The results showed that the β-amino esters had no appreciable activity, whereas the β-amino acids showed an increased post-synaptic evoked potency response (EPSP) in a dose-dependent manner. The active compounds showed the inverse activity when co-incubated with the DL-TBOA prototype, suggesting that they may act as direct or indirect agonists of post-synaptic glutamatergic receptors, possibly AMPA and NMDA. This activity may be useful in neurological and psychiatric disorders by acting on the restoration of synaptic function.